2014
DOI: 10.5348/ijhpd-2014-25-oa-13
|View full text |Cite
|
Sign up to set email alerts
|

A histopathological and histochemical study of cholecystitis

Abstract: histochemistry, composition of calculi and metaplasia, fibrosis and mucin histochemistry, fibrosis and stone composition indicated a decrease in intraepithelial total acid mucin content in chronic calculous cholecystitis. cases with severe inflammation showed the maximum decrease in sulfomucin, concomitant increase in sialomucin scores and a high incidence of gastric metaplasia. Intestinal metaplasia on other hand did not correlate with the degree of inflammation or sialomucin content. conclusion: this study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 22 publications
5
3
0
Order By: Relevance
“…In the present study, the most common age group affected was 31 to 40 years which is in concordance with other studies done by Anupama et al, Thamilselvi et al, and Mathur et al [ 6 - 8 ]. This age group predilection might be attributed to dyslipoproteinemia; as age progresses, there is an increase in the release of cholesterol into the bile associated with a decrease in bile synthesis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, the most common age group affected was 31 to 40 years which is in concordance with other studies done by Anupama et al, Thamilselvi et al, and Mathur et al [ 6 - 8 ]. This age group predilection might be attributed to dyslipoproteinemia; as age progresses, there is an increase in the release of cholesterol into the bile associated with a decrease in bile synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…A significant negative correlation was observed between an increase in grades of severity with a decrease in acidic mucin and sulfomucin of both superficial and deep epithelium, except sulfomucin in fibrosis. These findings were identical to the study conducted by Srivastava et al and Anupamaet al [ 1 , 6 ]. Pani et al found that a major amount of mucin in cholelithiasis and cholecystitis was sulfomucin and sialomucin, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations